2021 IEEE International Conference on Multimedia &Amp; Expo Workshops (ICMEW) 2021
DOI: 10.1109/icmew53276.2021.9455992
|View full text |Cite
|
Sign up to set email alerts
|

On Spammer Detection In Crowdsourcing Pairwise Comparison Tasks: Case Study On Two Multimedia Qoe Assessment Scenarios

Abstract: The last decade has brought a surge in crowdsourcing platforms' popularity for the subjective quality evaluation of multimedia content. The lower need for intervention during the experiment and more expansive participant pools of crowdsourcing platforms encourage researchers to join this trend. However, the unreliability of the participant behaviors puts a barrier in the wide adoption of these platforms. Although many works exist to detect unreliable observers in rating experiments, there is still a lack of me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…for ACR or Double Stimulus Impairment Scale (DSIS) scores. In case of binary answers, such as the expression of preference during a Pair Comparison (PC) test, recent works [16,17] favored the use of dissimilarity metrics (Rogers-Tanimoto (RT) dissimilarity [18], Cohen's Kappa Coefficient [19]) to estimate inter-observer agreement.…”
Section: Outlier Detection Methodsmentioning
confidence: 99%
“…for ACR or Double Stimulus Impairment Scale (DSIS) scores. In case of binary answers, such as the expression of preference during a Pair Comparison (PC) test, recent works [16,17] favored the use of dissimilarity metrics (Rogers-Tanimoto (RT) dissimilarity [18], Cohen's Kappa Coefficient [19]) to estimate inter-observer agreement.…”
Section: Outlier Detection Methodsmentioning
confidence: 99%
“…An early example of subjective IQA on crowdsourcing shows promise by comparing crowdsourcing and laboratory experiment results [12]. Recent works raise concerns on the effects of QoE tasks on crowdsourcing subjective experiments [13]. LIVE In the Wild [14] IQA dataset consists of over 350000 opinion scores on 1162 images.…”
Section: Related Workmentioning
confidence: 99%
“…Although several methodologies have been proposed for interobserver agreement and outlier detection in rating experiments [29], [30], there are not many well-established methodologies for ranking experiments. Ak et al [13] showed that inter-observer agreement in pairwise comparison experiments can be measured based on Rogers-Tanimoto (RT) dissimilarity measure. A similar variation to such metric, known as Jaccard index [31], has been developed by Paul Jaccard.…”
Section: Inter-observer Agreementmentioning
confidence: 99%
See 1 more Smart Citation
“…The main characteristics of these datasets are presented in Table I. 1) Exp-TMO Dataset: The Exp-TMO dataset has been recently published in [26]. This dataset contains originally 20 HDR sources processed with 4 different TMOs (see as Hypothetical Reference Circuits HRC) leading to a total of 120 pairs of tone mapped stimuli used in our experiment.…”
Section: A Datasetsmentioning
confidence: 99%